First description of OXA-48 carbapenemase harbored by Escherichia coli and Enterobacter cloacae from a single patient in Portugal - Manageiro, Vera (2015)
The blaOXA-48 gene has been detected in a variety of species and clones of Enterobacteriaceae, circulating mainly throughout the Mediterranean area but progressively disseminating to other geographical areas. To our knowledge, we describe here the first cases of OXA-48-producing Enterobacteriaceae in Portugal. Enterobacter cloacae and Escherichia coli were isolated from the urine of a catheterized patient.